A Fully Coupled Mechano-Electrochemical Model for All-Solid-State Thin-Film Li-Ion Batteries with Non-Porous Electrodes: Effects of Chemo-Mechanical Expansions on Battery Performance and Optimization Strategies for Stress Evolution. Issue 8 (1st August 2022) - Shao, Yu-qiang; Shao, Xiao-dong; Sang, Lin; Liu, Huan-ling
Abstract : A comprehensive and novel mechano-electrochemical coupling model for all-solid-state Li-ion batteries (ASSLBs) is developed, in particular, focusing on the influence of the volume changes caused by ions redistribution in the electrodes on the electrical and mechanical properties of the battery. The mathematical relationship between the partial molar volume and Poisson's ratio is determined for the condition of zero stress. The roles of the partial molar volumes of cathode and anode, the thickness and Young's modulus of the spacer are investigated. The results show that the electrode volume changes significantly during the charging and discharging process. Due to the mechanical imbalance, the confined cell generates considerable compressive stress (approximately 0.6 MPa). Reducing the partial molar volume of the anode can not only eliminate the compression stress but augment the capacity. Note that for the ASSLBs containing inorganic (oxide or sulfide) solid electrolytes (SEs), adjusting the material parameters to obtain proper compressive stress instead of a bulky cell holder may be another useful method to overcome the poor interface contact. Finally, by introducing polyurethane foam or other soft blocks with a suitable thickness and Young's modulus as spacers, the stress of the cell can be reduced by 79.33%.